Concentração letal média (CL50-96h) e efeitos subletais da amônia não ionizada sobre parâmetros hematológicos de alevinos de tambacu (Colossoma macropomum fêmea x Piaractus mesopotamicus macho) - Quaresma, Fabrízia da Silva (2016)
Ammonia is a toxic compound to aquatic organisms and at high concentrations in the water can cause various changes in the animal. Therefore, it becomes important to determine the tolerance of farmed aquatic animals for that substance. Thus, the aim of this study was to determine the median lethal concentration (LC50-96h) of un-ionized ammonia (NH3) in fingerlings tambacu (Colossoma macropomum x Piaractus mesopotamicus) in acute toxicity test and evaluate the effects of concentrations sublethal through the analysis of hematological parameters. In the acute toxicity test, the fingerl ings were exposed to ammonia at concentrations of: 0,09 (control); 0,54; 1,23; 2,52; 3 ,44 and 3,66 mg L-1NH3, which were obtained from the application of NH4Cl. The test lasted 96 hours and mortalities were recorded over that period. The LC50 was determin ed by statistical method Trimmed Spearman Karber . In sublethal exposure to ammonia test concentrations used were : 0,04 (control), 0,19 and 0,35mg L-1NH3.For analysis of hematological parameters, blood samples were collected before the addition of NH4Cl(timezero) and after 96 hours of exposure.The hematological parameters analyzed were: hematocrit ( Ht), hemoglobin(Hb), red blood cell count(RBC) mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration(MCHC). Data hematological parameters were subjected to analysis of variance (ANOVA) and when there was a significant difference between treatments , the averages were compared in pairs through the Tukey's HSD test (α=0,05).LC50-96h of theun - ionized ammonia (NH3) to fingerlings the hybrid tambacu was 1,63m g L-1. After 96h exposure to 0,35 mg L-1NH3, fish showed significant reductions in hematocrit and the MCV and significant increase in MCHC. Already Hb,RBC and MCH did not differ significantly between treatments and time 0. The exposure to fingerlins tambacu for short period to 0,19 mg L -1 of un-ionized ammonia (NH3) does not cause significant changes in hematological parameters of these fish.